Dukungan Keluarga dan Kepatuhan Diet Rendah Garam pada Penderita Hipertensi - Risky Rinawati; Nur Baharia Marasabessy (Poltekkes Kemenkes Maluku, 2022)
Hypertension is the most common disease suffered by the community. The trend of this disease is increasing from year to year. WHO data shows, a quarter of men and a fifth of women worldwide suffer from this disease. If not controlled, hypertension has an impact on damage to the heart, kidneys and risk of stroke. One effort to control hypertension that is easy and cheap is to do a low-salt diet. Family support plays an important role in increasing adherence to the recommended diet because the family is the closest unit to the patient. This study aims to determine the relationship between family support and adherence to a low-salt diet in hypertensive patients based on the literature review. The research method uses a narrative review. Search literature using certain keywords in two databases, Google Scholar and Pubmed, with full text article, publication year 2017-2022, research subjects are hypertensive sufferers, research article use cross sectional study design. Based on review form 10 articles found, there was a significant relationship between family support and adherence to a low-salt diet in patients with hypertension. The results indicate the importancy of family support for people with hypertension in improving low-salt diet complience.